Circovirus in Blood of a Febrile Horse with Hepatitis - Alvin Hui; Eda Altan; Nathan Slovis; Caitlin Fletcher; Xutao Deng; Eric Delwart (Viruses, 2021)
Circoviruses infect vertebrates where they can result in a wide range of disease signs or in asymptomatic infections. Using viral metagenomics we analyzed a pool of five sera from four healthy and one sick horse. Sequences from parvovirus-H, equus anellovirus, and distantly related to mammalian circoviruses were recognized. PCR identified the circovirus reads as originating from a pregnant mare with fever and hepatitis. That horse’s serum was also positive by real time PCR for equine parvovirus H and negative for the flavivirus equine hepacivirus. The complete circular genome of equine circovirus 1 strain Charaf (EqCV1-Charaf) was completed using PCR and Sanger sequencing. EqCV1 replicase showed 73–74% identity to those of their closest relatives, pig circoviruses 1/2, and elk circovirus. The closest capsid proteins were from the same ungulate circoviruses with 62–63% identity. The overall nucleotide identity of 72% to its closest relative indicates that EqCV1 is a new species in the Circovirus genus, the first reported in genus Equus. Whether EqCV1 alone or in co-infections can result in disease and its prevalence in different equine populations will require further studies now facilitated using EqCV1′s genome sequence.